Faith Unchanged: Spirituality, But Not Christian Beliefs and Attitudes, Is Altered in Newly Diagnosed Parkinson's Disease - Kéri, Szabolcs (Religions, 2016)
In this study, we aimed at investigating the validity and characteristics of the concept of hyporeligiosity in Parkinson's disease. Twenty-eight newly diagnosed, never-medicated patients with Parkinson's disease and 30 matched healthy control individuals received the Brief Multidimensional Measure of Religiousness/Spirituality (BMMRS), the Stolz's index of Christian religiosity, and the Francis Scale of Attitude to Christianity (FSAC). All participants identified themselves as Roman Catholic or Protestant. Parkinson's patients displayed decreased positive and negative spirituality on the BMMRS, whereas beliefs and attitudes related to their Christian religion were unchanged. The severity of the disease was associated with reduced spirituality, but not with Christian faith. These results suggest a dissociation between general spirituality and traditional religious faith in Parkinson's disease, which is consistent with the findings from patients with schizophrenia.